Motivation, Leadership, and Organizational Climate on Employee Performance: The Moderating Effect of Reward - Editya Nurdiana; Farah Noor Ayuningtyas (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing demand for transparent, effective, and accountable bureaucratic performance, along with inconsistent empirical findings regarding the determinants of employee performance, forms the basis of this research. This study aims to examine the effects of motivation, leadership, and organizational climate on employee performance, as well as to investigate the moderating role of reward within public sector organizations.  A quantitative approach with a cross-sectional design was employed, involving 115 employees of regional government agencies in Cirebon City selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM). The findings reveal that organizational climate is the only variable that has a significant effect on employee performance, while motivation and leadership do not demonstrate significant direct effects. Furthermore, reward does not significantly moderate the relationships between the independent variables and employee performance. The model also exhibits relatively low explanatory power. In conclusion, improving employee performance in the public sector is more effectively achieved through strengthening organizational climate rather than relying solely on motivational, leadership, or reward-based approaches that may not yet be optimally implemented.